The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11721-016-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of increasing robot group sizes on the human psychophysiological state in the context of human–swarm interaction

Abstract: We study the psychophysiological state of humans when exposed to robot groups of varying sizes. In our experiments, 24 participants are exposed sequentially to groups of robots made up of 1, 3 and 24 robots. We measure both objective physiological metrics (skin conductance level and heart rate), and subjective self-reported metrics (from a psychological questionnaire). These measures allow us to analyse the psychophysiological state (stress, anxiety, happiness) of our participants. Our results show that the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Controlling larger numbers of robots is likely to increase the cognitive load of the operator [31]. Cumulative cognitive load might be a function of attention required to supervise the robots [32], a robot's performance and autonomy when left unattended [33], and the need to manage dependencies between robots when they must coordinate to perform a task [34], in addition to other mission requirements such as communication with teammates.…”
Section: Operator Cognitive Loadmentioning
confidence: 99%
“…Controlling larger numbers of robots is likely to increase the cognitive load of the operator [31]. Cumulative cognitive load might be a function of attention required to supervise the robots [32], a robot's performance and autonomy when left unattended [33], and the need to manage dependencies between robots when they must coordinate to perform a task [34], in addition to other mission requirements such as communication with teammates.…”
Section: Operator Cognitive Loadmentioning
confidence: 99%
“…The model was able to predict a standard measure of situation awareness. Podevijn et al [114] study the psychophysiological state of the participants when they interact with a swarm of robots. A direct relationship was found between user state and number of robots which the user is exposed to and an increase in arousal value was observed when the user was exposed to 24 robots.…”
Section: Human Robot Interaction (Hri) Studiesmentioning
confidence: 99%
“…They found that human workload is not dependent on the number of robots when interacting with a robot swarm. Podevijn et al (2016) studied the effect of the robot swarm size on the human psychophysiological state. They found that higher robot swarm sizes provoke stronger psychophysiological responses.…”
Section: Related Literaturementioning
confidence: 99%
“…With the exception of Setter et al (2015) and Podevijn et al (2016), all the works that study the psychology of humans interacting with a robot swarm are performed in simulation only. Due to the inherent existence of the reality gap, though, it is not clear if human-swarm interaction studies performed in simulation only would provoke the same psychological reactions as the same human-swarm interaction studies performed with a robot swarm made up of real robots.…”
Section: Related Literaturementioning
confidence: 99%